1986
DOI: 10.1111/j.1439-0418.1986.tb00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture as mortality factor for cutworms, Agrotis segetum Schiff. (Lep., Noctuidae)

Abstract: The extreme fluctuations of cutworm attacks in Denmark have mainly been related to summer rainfall. In the present investigations the influence on the cutworms was split up and dealt with in the following three ways: Relative air humidity ‐ pilot experiments in the laboratory; rainfall ‐ semifield experiment with sprinkle irrigation of 2 m × 2 m plots; soil moisture ‐ greenhouse experiments using carrots in pots. No indications were found of the effect of the relative humidity or of the effects of falling rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…The difference in feeding frequency might even be bigger than could be revealed with the frequency of soil searching used. This result, obtained over a period of 4 days, corresponds very well with the increased mortality found among A. segetum larvae after about 10 days on moist soil with the same experimental set-up (ESBJERG et al 1986). Therefore a rather simple explanation may be suggested regarding the negative influence of excess summer precipitation on cutworm populations.…”
Section: 2supporting
confidence: 85%
See 2 more Smart Citations
“…The difference in feeding frequency might even be bigger than could be revealed with the frequency of soil searching used. This result, obtained over a period of 4 days, corresponds very well with the increased mortality found among A. segetum larvae after about 10 days on moist soil with the same experimental set-up (ESBJERG et al 1986). Therefore a rather simple explanation may be suggested regarding the negative influence of excess summer precipitation on cutworm populations.…”
Section: 2supporting
confidence: 85%
“…The present investigations show that under favourable dry conditions [BOVIEN and STAPEL (1934), MIKKELSEN and ESBJERG (1981) andESBJERG et al (1986)] 1st-and 2ndinstar A . segetum larvae will hide in the soil both day and night but interrupt the hiding 1-2 times during the day for about 1 h to enter the foliage of the plants and feed.…”
Section: Behavioural Aspectsmentioning
confidence: 49%
See 1 more Smart Citation
“…However, the most obvious effect from lack of shelter in the present investigation is the significantly lower mortality (Table 1) of small cutworms which could shelter in the vermiculite. This result corresponds on the one hand with shrinkage as sign of larval starvation after four days without shelter (Esbjerg, 1988) and on the other hand with the increased L~ -L 2 mortality, when there was moist soil around plants for 7-14 days (Esbjerg et al, 1986).…”
Section: Resultsmentioning
confidence: 72%
“…In the UK (Bowden et al, 1983) and the GDR (Ht~lbert, 1983), summer precipitation was found to be a major regulating factor, and in Denmark (Mikkelsen & Esbj erg, 1981) the numbers of days with precipitation in June and July were found to have a major negative influence on cutworm survival. Esbjerg et al (1986) showed soil moisture to be a mortality factor for young cutworms, but not for older (L 5 -L6) larvae (Esbjerg, in prep.). Further studies on young cutworms revealed that in dry soil, the small larvae leave the soil only for short periods to feed on the leaves of plants during the day (Esbjerg, 1988).…”
Section: Introductionmentioning
confidence: 99%